Development of the novel gene chip and restriction fragment length polymorphism (RFLP) methods for rapid detection of Mycobacterium tuberculosis complex in broth culture - Wen-Hung Wang; Chun-Yu Lin; Shu-Huei Jain; Po-Liang Lu; Yen-Hsu Chen (Journal of Microbiology, Immunology and Infection)
Background: Tuberculosis (TB) is a major global public health issue. Prompt and accurate TB diagnosis is crucial for starting appropriate treatments and preventing the disease's spread. Current diagnostic techniques are either slow or expensive. This study aimed to create and evaluate a new, fast, highly reliable, and cost-effective TB detection method using a gene chip and Restriction Fragment Length Polymorphism (RFLP) analysis on Mycobacteria Growth Indicator Tubes (MGIT) specimens. Methods: We assessed the effectiveness of a novel gene chip and RFLP methods targeting the 16S rRNA gene of Mycobacterium tuberculosis in 2000 MGIT culture-positive specimens. RFLP analysis identified the AfeI restriction site within the M. tuberculosis complex (MTBC) genome. Discrepancies were investigated through extensive sequencing and Cobas TaqMan PCR analysis, along with reviewing patient profiles. Results: Both methods showed high efficacy in detecting MTBC in broth cultures, with the gene chip method achieving a sensitivity of 99.27 %, specificity of 98.35 %, and the RFLP method showing a sensitivity of 98.18 %, specificity of 99.31 %. False negatives in two isolates were due to a mutation in the AfeI site. Additionally, five cases showed MTBC presence when nontuberculous Mycobacterium species grew in cultures. Conclusion: Our novel gene chip and RFLP methods are effective for rapid highly-reliable and cost-effective M. tuberculosis detection in MGIT specimens. Both gene chip and RFLP methods are suitable for resource-limited settings, offering an economical advantage. These methods have significant potential to improve clinical TB diagnosis.